Respiratory manifestations and management in children with Common Variable Immunodeficiency. (June 2016) - Pandit, Chetan; Hsu, Peter; van Asperen, Peter; Mehr, Sam
Summary: Common variable immunodeficiency is an antibody deficiency that usually presents in childhood with recurrent sino-pulmonary infections. Diagnostic delay is frequent and thus respiratory morbidity is common, ranging from recurrent suppurative bronchitis to bronchiectasis. Immunoglobulin replacement therapy is the mainstay of treatment, whilst prophylactic antibiotic therapy and muco-ciliary clearance are additional treatment options. This review examines the diagnosis and management of respiratory issues in children with CVID.